Interpretasi Salt Water-Fresh Water Zone menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner-Schlumberger di Desa Majasto dan Ponowaren, Kecamatan Tawangsari, Kabupaten Sukoharjo: Adha Nur Hidayat, Darsono, Darmanto - Adha Nur Hidayat, Adha Nur Hidayat; Darsono, Darsono; Darmanto, Darmanto (Jurnal Fisika dan Aplikasinya, 2025)
Research on interpretation of the salt water-fresh water zone using geoelectric resistivity Wenner-Schlumberger array has been conducted inMajasto village and Ponowaren village, Tawangsari District , Sukoharjo Regency. In These areas the well are contaminated by salt water. Measurements were performed using an Resistivitymeter OYO McOHM-EL 2119C models. The initial step conducted a preliminary survey to search for electrical conductivity (EC) with the depth of the wells as the sample, the results of the data were then processed with the software Surfer 11 to obtain the mapping of salt water-fresh water data. The next step was obtaining apparent resistivity data, the data obtained were processed using Res2Dinv software to 2 dimensional cross section model and Rockworks software showed 3 dimensional of the whole lines. Limitation between salt water-fresh water zone is predicted on the third line with position 1500 meters and a depth of 38.8 meters.